23 New and approved therapies for lupus nephritis: Belimumab and voclosporin. (6th April 2022) - Furie, Richard
Abstract : Our foray into novel therapies for lupus nephritis (LN) began in the first half of the 1990s. While the early development programmes ultimately failed, lessons learned from these studies paved the way for the successes of belimumab and voclosporin. The impetus to evaluate belimumab in LN was largely fueled by a post-hoc analysis of the BLISS-52 and BLISS-76 datasets that suggested improvement of kidney parameters in those patients who entered the Phase 3 programme with kidney abnormalities and who were randomized to belimumab. 1 BLISS-LN was the largest LN study ever performed and introduced several unique design features. The primary and key secondary endpoints were all successfully achieved. 2 3 The successful use of calcineurin inhibitors in LN justified studying voclosporin for this disease. Voclosporin had unsettling beginnings with a Phase 2 study where the mortality rate in the lower of the two dose groups was extraordinarily high. 4 Despite the observed efficacy, the safety signals created some degree of anxiety in moving forward. However, there was no uniform pattern to the deaths and furthermore, excessive mortality was not seen in the higher dose group. The Phase 3 study, known as AURORA, attained its primary endpoint as well as all key secondary endpoints. 5 In December 2020 the US FDA approved belimumab for the treatment of LN. This was a historical event in that belimumab was the very first drug approved for LN. One month later in January 2021, voclosporin received FDA approval. Not only will the availability of these two drugs improve LN response rates, their successful development programmes will provide inspiration to others that the challenges of drug development in LN can be overcome. References: Dooley MA, et al . Effect of belimumab treatment on renal outcomes: results from the phase 3 belimumab clinical trials in patients with SLE. Lupus 2013 Jan;22 (1):63–72. Furie R, et al . Two-Year, Randomized, Controlled Trial of Belimumab in Lupus Nephritis. N Engl J Med 2020 Sep 17;383 (12):1117–1128. Rovin BH, et al . A secondary analysis of the Belimumab International Study in Lupus Nephritis trial examined effects of belimumab on kidney outcomes and preservation of kidney function in patients with lupus nephritis. Kidney Int 2022 Feb;101 (2):403–413. Rovin BH, et al . A randomized, controlled double-blind study comparing the efficacy and safety of dose-ranging voclosporin with placebo in achieving remission in patients with active lupus nephritis. Kidney Int 2019 Jan;95 (1):219–231 Rovin BH, et al . Efficacy and safety of voclosporin versus placebo for lupus nephritis (AURORA 1): a double-blind, randomised, multicentre, placebo-controlled, phase 3 trial. Lancet 2021 May 29;397 (10289):2070–2080. Learning Objectives: Discuss the rationale for developing belimumab and voclosporin for lupus nephritis Explain lupus nephritis clinical trial results